2015
DOI: 10.1159/000430955
|View full text |Cite
|
Sign up to set email alerts
|

Management of Vision-Threatening Complications of Vasoproliferative Tumors of the Retina

Abstract: Aims: To report the management of vision-threatening complications of vasoproliferative tumors of the retina. Methods: Clinical records of 31 eyes of 30 patients treated at our centers from 1998 through 2013 were reviewed. The main outcome measures included: type of treatment, tumor regression, tumor relapse and final visual acuity. Results: Seventeen patients (57%) underwent vitrectomy for epimacular membranes (n = 10), rhegmatogenous retinal detachment (n = 2), vitreous hemorrhage (n = 2), tractional retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 23 publications
1
43
2
2
Order By: Relevance
“…Vitreoretinal surgery can be performed in patients with vitreous hemorrhage. 1,3,12,13,14,15 Of 160 patients with retinal detachment who underwent simultaneous cryotherapy and detachment surgery, 19 (12%) developed postoperative pigment shedding, while 7 (12%) of the 60 patients who did not undergo subretinal fluid drainage developed postoperative uveitis. 16 The same study reported that post-cryotherapy uveitis occurred in an average of 5-8 days.…”
Section: Discussionmentioning
confidence: 99%
“…Vitreoretinal surgery can be performed in patients with vitreous hemorrhage. 1,3,12,13,14,15 Of 160 patients with retinal detachment who underwent simultaneous cryotherapy and detachment surgery, 19 (12%) developed postoperative pigment shedding, while 7 (12%) of the 60 patients who did not undergo subretinal fluid drainage developed postoperative uveitis. 16 The same study reported that post-cryotherapy uveitis occurred in an average of 5-8 days.…”
Section: Discussionmentioning
confidence: 99%
“…The most common anterior segment complication in eyes with VPT was glaucoma. 7 One patient had complicated neovascular glaucoma due to peripheral anterior synechia and neo-vascularization in the iris and angle. 9 After receiving VT and tumor resection, the intraocular pressure was normalized.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 4 5 6 Most patients suffer from visual symptoms that are secondary to leakage and inflammation of this peripheral vascular tumor, such as decreased vision, floater, distortion, or photopsia. 7 8 Without dilating the pupil and checking the peripheral retina, the VPT might be missed. Visual acuity (VA) varied from light perception to 6/6, depending on the complications of VPT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sie sind jedoch meist nicht peripher, sondern zentraler lokalisiert. Die Behandlung vasoproliferativer Tumoren ist abhängig von der Größe der Läsion und dem Vorhandensein sekundärer Komplikationen [1,2,6]. Asymptomatische und kleine Tumoren, die überwiegend bei Routineuntersuchungen als Zufallsbefund diagnostiziert werden, zeigen oft nur eine geringere Progression und sollten daher zunächst beobachtet werden.…”
Section: Schlussfolgerungunclassified